Lesiones músculo-esqueléticas de hombro en usuarios de silla de ruedas - Bueno B., Daniel; Amador C., Paola (Revista Hospital Clínico Universidad de Chile, 2018)
Manual wheelchair is one the most used mobility device in people that is unable to walk.It enhances functional independence in non ambulant people, but it costs a great energyexpenditure and is a source of painful musculoskeletal injuries. The most frequently affectedjoint in manual wheelchair users is the shoulder (rotator cuff tendinopathy and subacromialimpingement). In this review, we aim to describe the risk factors and biomechanical issues thatmake wheelchair users more prone to develop shoulder pain. Further, we discuss potencialapproaches for the prevention and early treatment of these injuries.